The Mouse SAGE Site: database of public mouse SAGE libraries - Divina, Petr; Forejt, Jirí (Nucleic acids research, 2004)
The Mouse SAGE Site is a web-based database of all available public libraries generated by the Serial Analysis of Gene Expression (SAGE) from various mouse tissues and cell lines. The database contains mouse SAGE libraries organized in a uniform way and provides web-based tools for browsing, comparing and searching SAGE data with reliable tag-to-gene identification. A modified approach based on the SAGEmap database is used for reliable tag identification. The Mouse SAGE Site is maintained on an ongoing basis at the Institute of Molecular Genetics, Academy of Sciences of the Czech Republic and is accessible at the internet address http://mouse.biomed.cas.cz/sage/.
Keywords: Databases, Genetic; Mice; Information Storage and Retrieval; Computational Biology; Animals; internet; myši; Česká republika; Gene Expression Profiling; Internet; databáze genetické; Czech Republic; zvířata; ukládání a vyhledávání informací; stanovení celkové genové exprese; genová knihovna; výpočetní biologie; Gene Library